Europe, where do you go? - Marsili, M. (Europea, 2023)
The Russian-Ukrainian conflict, which started in 2014 after the annexation of Crimea to the Russian Federation, and re-flamed in February 2022 with the “special military operation” in the Donbas, shows the weaknesses and shortcomings of the European Un- ion: the east-west enlargement, the lack of an autonomous foreign policy, the absence of a European defense and security ownership and the dependence on NATO. This short article aims to shed light on the major problems of the European Union in the context of the Ukrainian crisis.